Information system for determining the effect of air pollution on trace elements relations in vegetables - Высоцкая, Елена Владимировна; Некос, Алла Наумовна; Беспалов, Юрий Гаврилович; Носов, Константин Валентинович; Петухова, Алена Леонидовна (Technology audit and production reserves, 2013)
The paper is devoted to the development of the information system for determining the influence of air pollution on the microelements relations in plant food (vegetables). The block diagram of the information system includes computer, interface, spectrophotometer, user. The computer unit includes data input/output units, data processing unit, DB (database) and data analysis unit. One of the main units of the IS system is the data analysis unit, which consists of three parts: assessment of the influence of natural and anthropogenic factors on the concentration of heavy metals in plant products using the analysis of variance, determination of the concentration of heavy metals in plant food products using the method of discriminant functions and determination of the effect of air pollution on the microelements relations in ground vegetables using the unit for discrete simulation of dynamic systems. As a result of the IS system operation, the graphs of relations between microelements in potato tubers were obtained.